Cost-effective methods for evaluation of neighbourhood renewal programs - Wood, Gavin; Cigdem, M. (2012)
An important goal of the National Housing Reform Agenda is to ‘reduce concentrations of disadvantage that exist in some social housing estates’ (AHURI 2011, p.3). There is a growing body of Australian evidence indicating that the stigmatisation of housing in poorer neighbourhoods is associated with inferior access to health and education services and relatively low levels of wellbeing (Bridge et al. 2003; Stone & Hulse 2007; Hulse & Saugeres 2008). This has motivated Australian State Housing Authorities to introduce Neighbourhood Renewal programs to improve housing quality and strengthen service delivery within disadvantaged communities that have concentrations of social housing. These programs aim to generate positive non-shelter outcomes and strengthen social cohesion within targeted communities. This project aims to design and implement a robust quasi-experimental methodology for the evaluation of urban renewal programs. This is not the first Australian attempt at such an evaluation; but this proposal departs from previous survey based studies (Wood 2002; Randolph et al. 2004; Walker et al. 2007), by using quantitative techniques to arrive at financial measures of the non-shelter benefits generated by renewal programs. It is not put forward as an alternative to existing approaches to the evaluation of Australian neighbourhood renewal programs. We suggest these quasi-experimental methods be viewed as a complement to evaluations using community surveys and administrative data. The approach has a sound conceptual basis grounded in economic analyses of housing markets showing that, if renewal programs yield benefits such as improved physical appearance, reductions in crime, vandalism and so on, the demand for private housing in and around the targeted areas will increase. The favourable shift in demand will increase house prices struck on transactions in post-Neighbourhood Renewal periods (Zielenbach, Voith & Mariano 2010; Rossi-Hansberg, Sarte & Owens 2010). In short, if there are benefits they will generate house price premiums.